2009
DOI: 10.1007/s12192-008-0055-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heat shock protein 60 in the tissues of transported piglets

Abstract: In this study, we sought to determine the distribution and expression of heat shock protein 60 (Hsp60) in the tissues of transported piglets. A total of 24 Chinese Erhualian piglets with an average body weight of 20±1 kg were assessed under both 2-h transported and normal housing conditions. Results of enzymatic analysis showed that the serum creatine kinase and aspartate aminotransferase concentrations were significantly increased in the 2-h transported piglets. Acute cellular lesions characterized by granula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
(35 reference statements)
1
18
1
Order By: Relevance
“…All Hsp110 loss-of-function or deletion mutants listed in the Drosophila deletion project database are lethal (Easton et al, 2000). However, contrary to our finding of Hsp110 protecting myocardial cells from damage, Hsp110 expression is induced by cadmium exposure but is dispensable for cell survival of mouse NIH3T3 fibroblasts (Ridley et al, 2010), suggesting that the regulation of Hsp110 may have cellular and tissue specificity in disparate organisms (Zhu et al, 2009;Yue et al, 2010).…”
Section: Discussioncontrasting
confidence: 82%
“…All Hsp110 loss-of-function or deletion mutants listed in the Drosophila deletion project database are lethal (Easton et al, 2000). However, contrary to our finding of Hsp110 protecting myocardial cells from damage, Hsp110 expression is induced by cadmium exposure but is dispensable for cell survival of mouse NIH3T3 fibroblasts (Ridley et al, 2010), suggesting that the regulation of Hsp110 may have cellular and tissue specificity in disparate organisms (Zhu et al, 2009;Yue et al, 2010).…”
Section: Discussioncontrasting
confidence: 82%
“…Bao et al (2008) reported an attenuation of four cardiac Hsp members, in response to 6 h road transportation. In accordance with this study, Zhu et al (2009) found more than 60% reduction in cardiac Hsp60 of piglets, following 2 h transportation. Most interestingly, the authors report a tissue-specific Hsp response; in addition to the decrease in cardiac Hsp, a significant increase and nonchanged levels of Hsp60 were detected for the stomach, liver and kidney, respectively.…”
Section: Lt-epoxide (% Of Lt)supporting
confidence: 91%
“…Recently, it has been reported that elevated levels of intracellular Hsp60 may confer a tissue-dependent cytoprotection in 2-h transported piglets (Zhu et al, 2009). Studies during the last decade indicated that extracellular Hsp, being released from stressed cells, promoted proinflammatory cytokine production and local inflammation through activation of the innate immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Frozen intestinal mucosa samples were homogenized in cold solution (200 mg tissues per milliliter) containing 0.15 M NaCl, 20 mM Tris-HCl (pH 8.0), 1 mM EDTA, 1 mM phenylmethylsulfonyl fluoride, 0.1 μM E-46, 0.08 μM aprotinin, 0.1 μM leupeptin, and 0.1% NP-40 (Salokhe et al 2006;Zhu et al 2009) using Ultra-Turrax homogenizer on ice. The homogenate was centrifuged at 1,200×g, 15 min at 4°C.…”
Section: Semiquantitative Detection Of Hsp70 By Enzyme-linked Immunosmentioning
confidence: 99%